Strategi Pemimpin Gereja dalam Pemberdayaan Potensi Ekonomi di Gereja Toraja Jemaat Banula - Irma Tarru’ Padang; Destalia Destalia; Karlina Komba’; Junita Ronang; Frans Toding; Bunga Mesa Arruan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The economic empowerment of the congregation is also part of the church's duties and callings, the church is not limited to spiritual strengthening but also about the real life of the congregation. For this reason, this study aims to find strategies that can be carried out by the Toraja church, the Banula congregation, in increasing the potential for economic empowerment within the congregation. To achieve this purpose, the author uses a qualitative research method with a literature study and social analysis model. The literature study was obtained from secondary data originating from books, articles/journals and relevant internet sources. Meanwhile, data obtained from the field is primary data based on observation and interviews. The theory used in this study is about empowerment, the theory of strategy and the theory of leadership. The results of the study are that the church has begun the foundation in economic empowerment and will continue to be improved to the next stage. Considering the natural potential and individual potential in the Toraja church, the Banula congregation is quite important to be developed.